Characteristics of x-ray attenuation in electrospun bismuth oxide/polylactic acid nanofibre mats - Noor Azman, Nurul; Siddiqui, Salim; Haroosh, Hazim; Albetran, Hani; Johannessen, B.; Dong, Yu; Low, It (Blackwell Publishing, 2013)
The characteristics of the X-ray attenuation in electrospun nano(n)- and micro(m)-Bi2O3/polylactic acid (PLA) nanofibre mats with different Bi2O3 loadings were compared as a function of energy using mammography (i.e. tube voltages of 22–49 kV) and X-ray absorption spectroscopy (XAS) (7–20 keV). Results indicate that X-ray attenuation by electrospun n-Bi2O3/PLA nanofibre mats is distinctly higher than that of m-Bi2O3/PLA nanofibre mats at all energies investigated. In addition, with increasing filler loading (n-Bi2O3 or m-Bi2O3), the porosity of the nanofibre mats decreased, thus increasing the X-ray attenuation, except for the sample containing 38 wt% Bi2O3 (the highest loading in the present study). The latter showed higher porosity, with some beads formed, thus resulting in a sudden decrease in the X-ray attenuation.